The effectiveness of socially sustainable sourcing mechanisms: Assessing the prospects of a new form of joint regulation. Issue 1 (14th January 2013) - Wright, Chris F.; Brown, William
Abstract The traditional mechanisms for improving and protecting labour standards in advanced economies are failing. In Britain, the effectiveness of collective bargaining has diminished substantially over the past quarter century. Legally enforceable minimum labour standards have been an inadequate substitute. A new form of 'joint regulation' is emerging that may be better attuned to the contemporary structure of product market competition. It involves employers and unions coordinating action on labour standards across the supply chains of firms that contribute to the production of a particular good or service. This article explores the circumstances in which these 'socially sustainable sourcing' mechanisms develop and examines their impact on labour standards, by means of two case studies.